Identification of wheat stem rust resistance genes in wheat cultivars from Hebei province, China - Sun, Huiyan; Wang, Ziye; Wang, Rui; Chen, Si; Ni, Xinyu; Gao, Fu; Zhang, Yazhao; Xu, Yiwei; Wu, Xianxin; Li, Tianya (Frontiers in Plant Science, 2023)
Wheat stem rust is caused by Puccinia graminis f. sp. tritici. This major disease has been effectively controlled via resistance genes since the 1970s. The appearance and spread of new races of P. graminis f. sp. tritici (eg., Ug99, TKTTF, and TTRTF) have renewed the interest in identifying the resistance gene and breeding cultivars resistant to wheat stem rust. In this study, gene postulation, pedigree analysis, and molecular detection were used to determine the presence of stem rust resistance genes in 65 commercial wheat cultivars from Hebei Province. In addition, two predominant races 21C3CTHTM and 34MRGQM were used to evaluate the resistance of these cultivars at the adult-plant stage in 2021–2022. The results revealed that 6 Sr genes (namely, Sr5, Sr17, Sr24, Sr31, Sr32, Sr38, and SrTmp), either singly or in combination, were identified in 57 wheat cultivars. Overall, 36 wheat cultivars contained Sr31. Sr5 and Sr17 were present in 3 and 3 cultivars, respectively. Gao 5218 strong gluten, Jie 13-Ji 7369, and Kenong 1006 contained Sr24, Sr32, and Sr38, respectively. No wheat cultivar contained Sr25 and Sr26. In total, 50 (76.9%) wheat cultivars were resistant to all tested races of P. graminis f. sp. tritici in field test in 2021–2022. This study is important for breeding wheat cultivars with resistance to stem rust.